2018
DOI: 10.1155/2018/4520294
|View full text |Cite
|
Sign up to set email alerts
|

Effective Immunotherapy in Bone Marrow Metastatic Melanoma Presenting with Disseminated Intravascular Coagulopathy

Abstract: Malignant melanoma is responsible for the majority of skin cancer deaths and is increasing in prevalence. Bone marrow (BM) involvement by melanoma is rare in the absence of widespread visceral disease. Here, we report the case of a 30-year-old female who presented to the hospital with back pain, low-grade fever, and easy bruising. She was found to be bicytopenic and in disseminated intravascular coagulopathy (DIC). Surprisingly, BM biopsy showed extensive involvement by metastatic malignant melanoma in the abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 51 publications
1
5
0
4
Order By: Relevance
“…is report describes the second case of DIC in a patient with metastatic melanoma treated with immunotherapy, but the first case affecting the mucosa. Gbadamosi et al [6] reported a case of bone marrow metastatic melanoma presenting with DIC.…”
Section: Discussionmentioning
confidence: 99%
“…is report describes the second case of DIC in a patient with metastatic melanoma treated with immunotherapy, but the first case affecting the mucosa. Gbadamosi et al [6] reported a case of bone marrow metastatic melanoma presenting with DIC.…”
Section: Discussionmentioning
confidence: 99%
“…Bizim vakamız morfolojik ve immünhistokimyasal yönden metastatik malign melanom ile tamamen uyumluydu. Metastatik malign melanomlu hastaların primer lezyonu %52 oranla kutanöz lezyondur (7). Bu hastalarda bel ağrısı (en sık), halsizlik, peteşi sık rastlanan bulgulardır (7).…”
Section: Discussionunclassified
“…Metastatik malign melanomlu hastaların primer lezyonu %52 oranla kutanöz lezyondur (7). Bu hastalarda bel ağrısı (en sık), halsizlik, peteşi sık rastlanan bulgulardır (7). Hastamızın 15 gün öncesine kadar başka bir semptomu yoktu.…”
Section: Discussionunclassified
See 2 more Smart Citations